Ceiling fan air speeds around desks and office partitions. (1st November 2017) - Gao, Yunfei; Zhang, Hui; Arens, Edward; Present, Elaina; Ning, Baisong; Zhai, Yongchao; Pantelic, Jovan; Luo, Maohui; Zhao, Lei; Raftery, Paul; Liu, Shichao
Abstract: Ceiling fans may cool room occupants very efficiently, but the air speeds experienced in the occupied zone are inherently non-uniform. Designers should be aware of several generic flow patterns when positioning ceiling fans in a room. Key to these are the fan jet itself and lateral spreading near the floor. Adding workstation furniture redirects the jet's airflow laterally in a deeper spreading zone, making room air flows more complex but potentially increasing the cooling experienced by the occupants. This paper presents the first evaluation of the effects of tables and workstation partitions on a room's generic air flow and comfort profiles. In a test room with a ceiling fan, we moved five anemometers mounted in a "tree" at heights of 0.1, 0.6, 0.75, 1.1, and 1.7 m to sample a dense measurement grid of 7 rows and 6 columns. We tested five different table and partition configurations and compared them to the empty room base case. From the results we propose a simplified model of room airflow under ceiling fans, useful for positioning fans and workstation furniture. We also present comfort contours measured in two ways that have comfort standards implications. The measured data are publicly available on the internet. Highlights: We performed high resolution measurements of ceiling-fan-induced air flow in an empty room. We measured air flow profiles in this same room with five table and partition configurations and all data are appended. The initial ceiling fan air flow in the room could be modeled as a free jet. Room circulation, with and without tables and partitions, may be represented by a simplified intuitive model for designers. We quantify the distribution of comfort cooling provided by fan air flow in the room using the metric 'corrective power'.